BIG DATA IN EDUCATION: POTENTIAL, IMPLEMENTATION, AND IMPLICATIONS - Loso Judijanto; Nurul Aini (International Journal of Teaching and Learning, 2023)
This research explores the potential, implementation and implications of big data in education. Big data has the potential to improve the quality of education through personalised learning and advanced data analytics, enabling more optimised curricula and early intervention for student learning difficulties. However, big data implementation faces significant challenges related to data privacy and security, as well as the need to train educators in data analysis skills. Adequate technological infrastructure is also an important prerequisite. Overall, the use of big data in education promises great benefits, but it must be done with a cautious approach and consider ethical aspects, security and proper training.